Pendidikan Sebagai Upaya Pemerdekaan Manusia - Paulinus Kanisius Ndoa; Stefanus Hulu (Jurnal Magistra, 2023)
Today, the world of education is experiencing a shift from its true values. The education system used places too much emphasis on intellectual aspects, textual values, and charitable morality. However, they pay less attention to aspects of personal character formation, value education, and sensitivity and social responsibility. This situation should not be allowed to continue. Now is the time for stakeholders who are involved in organizing education to return education to the "spirit" idealized by the father of national education, Ki Hajar Dewantara, regarding education that is free. This paper is the result of exploring Ki Hajar Dewantara's ideas on education. Done by using literature review. From the results of a literature search it was concluded that education that liberates will produce three types of people. First, it will give birth to humans who are not ruled by other people, but their minds can rule themselves. Second, giving birth to humans who stand tall because of their own strength. Third, to give birth to human beings who are capable of self-discipline, so that they do not interfere with the independence of others.